Histone H3.3 sub-variant H3mm7 is required for normal skeletal muscle regeneration - Akihito Harada (Nature Portfolio, 2018)
Incorporation of histone H3 variant H3.3 into chromatin regulates transcription. Here the authors find that H3.3 sub-variant H3mm7 is required for skeletal muscle regeneration and that H3mm7 nucleosomes are unstable and exhibit higher mobility, with H3mm7 promoting open chromatin around promoters.